Ageing alters the impact of nutrition on immune function - Yaqoob, Parveen (Proceedings of the Nutrition Society, 2017)
Immunosenescence during ageing is a major challenge which weakens the ability of older individuals to respond to infection or vaccination. There has been much interest in dietary strategies to improve immunity in older people, but there is an assumption that modulation of the immune response in older people will be based on the same principles as for younger adults. Recent evidence suggests that ageing fundamentally alters the impact of nutrition on immune function. As a result, interpretation of data from studies investigating the impact of diet on immune function is highly dependent on subject age. Study design is critically important when investigating the efficacy of dietary components, and most studies involving older people include rigorous inclusion/exclusion criteria based on medical history, laboratory tests, general health status and often nutritional status. However, immunological status is rarely accounted for, but can vary significantly, even amongst healthy older people. There are several clear examples of age-related changes in immune cell composition, phenotype and/or function, which can directly alter the outcome of an intervention. This review uses two case studies to illustrate how the effects of n-3 PUFA and probiotics differ markedly in young v. older subjects. Evidence from both suggests that baseline differences in immunosenescence influence the outcome of an intervention, highlighting the need for detailed immunological characterisation of subjects prior to interventions. Finally, future work elucidating alterations in metabolic regulation within cells of the immune system as a result of ageing may be important in understanding the impact of diet on immune function in older people.